Direct measurement of oscillatory RhoA activity in embryonic cortical neurons stimulated with the axon guidance cue netrin‐1 using fluorescence resonance energy transfer. (10th February 2016) - Antoine‐Bertrand, Judith; Fu, Min; Lamarche‐Vane, Nathalie
Research article: Using fluorescence resonance energy transfer, we visualised RhoA activity oscillations in live dissociated embryonic cortical neurons. We show that the addition of the axon guidance cue netrin‐1 modulates the pattern of RhoA oscillations for a short period of time in whole neurons. In addition, netrin‐1 transiently increased RhoA activity, specifically in the growth cones. Here, we propose that global inhibition of RhoA by netrin‐1 is preceded by short‐term region‐specific RhoA activation, including the neuronal growth cone. Abstract : Background Information: Rho GTPases play an essential role during the development of the nervous system. They induce cytoskeletal rearrangements that are critical for the regulation of axon outgrowth and guidance. It is generally accepted that Rac1 and Cdc42 are positive regulators of axon outgrowth and guidance, whereas RhoA is a negative regulator. However, spatiotemporal control of their activity can modify the function of Rho GTPases during axonal morphogenesis. Signalling downstream of the axon guidance cue netrin‐1 and its receptor deleted in colorectal cancer (DCC) triggers the activation of Rac1 and the inhibition of RhoA to promote axon outgrowth. However, our previous work also suggests that netrin‐1/DCC signalling can activate RhoA in a time‐ and region‐specific manner. Results: Here, we visualised RhoA activation in response to netrin‐1 in live embryonic cortical neurons using fluorescence resonance energy transfer. RhoA activity oscillated in unstimulated neurons and netrin‐1 increased the amplitude of the oscillations in growth cones after 5 min of stimulation. Within this period of time, netrin‐1 transiently increased RhoA activity and modulated the pattern of RhoA oscillations. We found that the timing of netrin‐1‐induced RhoA activation was different in whole neurons, cell bodies and growth cones. Conclusions: We conclude that netrin‐1 modulates the spatiotemporal activation of RhoA in embryonic cortical neurons. Significance: This study demonstrates for the first time the short‐term localised activation of RhoA in neuronal growth cones by the axon guidance cue netrin‐1.